Limiting and Withdrawing Life Support in the PICU: For Whom Are These Options Discussed?*. Issue 2 (February 2016) - Keele, Linda; Meert, Kathleen L.; Berg, Robert A.; Dalton, Heidi; Newth, Christopher J. L.; Harrison, Rick; Wessel, David L.; Shanley, Thomas; Carcillo, Joseph; Morrison, Wynne; Funai, Tomohiko; Holubkov, Richard; et al.
Abstract : Objectives: Most deaths in U.S. PICUs occur after a decision has been made to limitation or withdrawal of life support. The objective of this study was to describe the clinical characteristics and outcomes of children whose families discussed limitation or withdrawal of life support with clinicians during their child's PICU stay and to determine the factors associated with limitation or withdrawal of life support discussions. Design: Secondary analysis of data prospectively collected from a random sample of children admitted to PICUs affiliated with the Collaborative Pediatric Critical Care Research Network between December 4, 2011, and April 7, 2013. Setting: Seven clinical sites affiliated with the Collaborative Pediatric Critical Care Research Network. Patients: Ten thousand seventy-eight children less than 18 years old, admitted to a PICU, and not moribund at admission. Interventions: None. Measurements and Main Results: Families of 248 children (2.5%) discussed limitation or withdrawal of life support with clinicians. By using a multivariate logistic model, we found that PICU admission age less than 14 days, reduced functional status prior to hospital admission, primary diagnosis of cancer, recent catastrophic event, emergent PICU admission, greater physiologic instability, and government insurance were independently associated with higher likelihood of discussing limitation or withdrawal of life support. Black race, primary diagnosis of neurologic illness, and postoperative status were independently associated with lower likelihood of discussing limitation or withdrawal of life support. Clinical site was also independently associated with likelihood of limitation or withdrawal of life support discussions. One hundred seventy-three children (69.8%) whose families discussed limitation or withdrawal of life support died during their hospitalization; of these, 166 (96.0%) died in the PICU and 149 (86.1%) after limitation or withdrawal of life support was performed. Of those who survived, 40 children (53.4%) were discharged with severe or very severe functional abnormalities, and 15 (20%) with coma/vegetative state. Conclusions: Clinical factors reflecting type and severity of illness, sociodemographics, and institutional practices may influence whether limitation or withdrawal of life support is discussed with families of PICU patients. Most children whose families discuss limitation or withdrawal of life support die during their PICU stay; survivors often have substantial disabilities.